Hemoglobin and clinical outcomes of in-hospital patients with severe acute exacerbation of chronic obstructive pulmonary disease: a multicenter cohort study - Wu, Suji; Yi, Qun; Luo, Yuanming; Wei, Hailong; Ge, Huiqing; Liu, Huiguo; Li, Xianhua; Zhang, Jianchu; Pan, Pinhua; Yi, Mengqiu; Cheng, Lina; Zhou, Hui; et al. (Frontiers in Medicine, 2025)
BackgroundHemoglobin is one of the most common laboratory tests for hospitalized patients, and both anemia and polycythemia are common comorbidities in severe acute exacerbation of chronic obstructive pulmonary disease (AECOPD). However, limited evidence focuses on the predictive value of anemia or polycythemia for in-hospital adverse outcomes of severe AECOPD.MethodsThe patients hospitalized for severe AECOPD were prospectively enrolled from 10 medical centers in China. They were categorized into three groups: anemia, normal, and polycythemia, based on their hemoglobin levels on-admission. The adverse outcomes which included all-cause in-hospital mortality, invasive ventilation, and intensive care unit (ICU) admission.ResultsA total of 9,660 AECOPD inpatients were included. The cohort identified a significant association between anemia and adverse outcomes when compared to the normal group (5.20% vs. 2.80%, p < 0.001), including In-hospital mortality (1.12% vs. 0.29%, p < 0.001), invasive ventilation (2.12% vs. 1.19%, p = 0.001), ICU admission (4.24% vs. 2.41%, p < 0.001). When hemoglobin was further categorized from <6 g/dL to ≥20 g/dL, and 12 to <16 g/dL was taken as reference, ORs for adverse outcomes increased with decreased hemoglobin in the overall cohort, hemoglobin<60 g/dL (OR = 7.714, 95% CI: 2.622 20.887), hemoglobin 6 to <9 g/dL (OR = 3.284, 95% CI: 2.142 4.93). Conversely, no significant relationship was observed between polycythemia and adverse outcomes when compared to the normal group. Additionally, compared with normal group, participants with anemia were found to be older and showed elevated levels of WBC, Neutrophil ratio, PCT, CRP, serum G test positive rate, GM test positive rate, BUN, creatinine and D-dimer.ConclusionWhile there is no effect of polycythemia on adverse outcomes in severe AECOPD inpatients, anemia on-admission, particularly <9 g/dL, is associated with a heightened risk of adverse outcomes, which may serve as an effective biomarker of poor prognosis among inpatients with severe AECOPD.